We who cannot be daughters - Militante, Clarissa V. (University of Santo Tomas Publishing House, 2014)
"Elena Tacio was supposed to have started her family's curse: the mothers would not be real mothers and the daughters cannot be daughters, as the mother dies upon giving birth to a daughter. Elena fell in love with a Spanish Alferez and betrayed her husband, who fought with the wine toddy conspirators against the Spanish friar and officials. The Elena-Alferez affair would produce a daughter, who would be named Maria. The girl would be born on the eve of the departure of the friars from the islands because of an uprising. Elena's friend, the Chinese mestizo migrant Sito, would take Maria to the city and take care of her. The two would be separated and Maria would be adopted by Theodore, an American missionary-turned-businessman. He would rename her Maria Sarah. Maria Sarah would also grow up believing she was indeed an American daughter, though she had always felt that something was not right with her. Sarah's destiny would eventually be revealed to her in a dream, and she would understand her fate. Her transgression would be her betrayal of her two friends Roberto and Auring. From Maria Sarah would descend future daughters, Laura, born in the time of Japanese Occupation, and Carmen, who would be born in the time of political chaos under an authoritarian government. They would also know about the stories of their ancestors and their destinies through the dream; but their understanding of their past would remain fragmented. They would commit their own transgressions, because that is what their dream has always counseled. Carmen though would not understand her fate and instead of the one committing the betrayal, she would be betrayed."--Back cover.